Perancangan Aplikasi Kepuasan Mahasiswa Terhadap Dosen Fakultas Teknik Universitas Islam Makassar Menggunakan Metode Simple Additive Weighting - Husain, Nursuci Putri; Baco, Syarifuddin (Journal of System and Computer Engineering, 2024)
Faculty of Engineering UIM is one of the faculties at private universities in Makassar City. Currently, measuring student satisfaction with lecturers by filling out questionnaires through google forms. Disadvantages in filling out google forms because you can use gmail freely so that data manipulation can occur. So that a web application is created that facilitates student access and participation in providing assessments of lecturer performance. The purpose of the study was to design a web-based student satisfaction application for lecturers to increase student participation and produce more representative assessments. Waterfall research method as an application development method from the needs analysis, design, implementation, testing and maintenance phases while the Simple Additive Weighting method functions in the decision-making process. The results of application research where students log in to enter the dashboard page that displays a list of lecturers. On the lecturer list page there is a list of questions in assessing lecturer performance while on the admin page there is a menu that displays the results of the SAW calculation with a scale of 20 - 100 information is not good, not good, good enough, good and very good. Conclusion The application is able to provide solutions in mapping, understanding and assessing student satisfaction performance with lecturers in improving the quality of learning with a user-friendly interface. Keywords : Satisfaction, Simple Additive Weighting, Website